Pyriculariose resistant rice - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
Rice pyriculariose poses a serious constraint to rice production throughout Africa, particularly in those regions subject to drought: more than half of the rice grown in Africa on about 2,500,000 ha (6 million acres) is cultivated in this type...